Incidental finding of aberrant subclavian artery during computed tomography scan - Yusof, Mubarak Mohd; Shamsudin, Sharini (Journal of Kathmandu Medical College, 2015)
Two cases of aberrant subclavian arteries were detected incidentally during computed tomography scan of the thorax for other medical conditions. The patients did not have weight loss or dysphagia lusoria. The origin and course of the aberrant subclavian arteries are related to the anomaly of the aortic arch. The variations of aberrant right subclavian artery with left aortic arch and aberrant left subclavian artery with right aortic arch on computed tomography are discussed. Journal of Kathmandu Medical College Vol. 3, No. 4, Oct.-Dec., 2014 Page: 162-164